2003
DOI: 10.1046/j.1365-294x.2003.01776.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of lemmings (Lemmus): no evidence for postglacial colonization of Arctic from the Beringian refugium

Abstract: Beringia is considered as an important glacial refugium that served as the main source for colonization of formerly glaciated Arctic regions. To obtain high resolution views of Arctic refugial history, we examined mitochondrial cytochrome b phylogeography in the northern genus of rodents, Lemmus (true lemmings), sampled across its circumpolar distribution. Strong phylogeographical structure suggests vicariant separation over several glacial-interglacial periods and does not provide evidence supporting the impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(120 citation statements)
references
References 39 publications
5
114
1
Order By: Relevance
“…Note that the microsatellite admixture is calculated at the population level, while mtDNA admixture refers to the frequency of Lota l. lota (EB lineage) or L. l. maculosa (NA lineage) mtDNA in individuals in the population. Rhymer et al 2001;Fedorov et al 2003), though subspecies of closely related temperate fish are often found to interbreed freely at contact zones (reviewed in Utter 2001;Lutz-Carrillo et al 2006;Taylor et al 2007). In fact, interbreeding when no geographic barrier prevails is fundamental to the definition of fish subspecies (Nelson 1999;Haig et al 2006).…”
Section: Ecological Parapatry and Subspecies Differencesmentioning
confidence: 99%
“…Note that the microsatellite admixture is calculated at the population level, while mtDNA admixture refers to the frequency of Lota l. lota (EB lineage) or L. l. maculosa (NA lineage) mtDNA in individuals in the population. Rhymer et al 2001;Fedorov et al 2003), though subspecies of closely related temperate fish are often found to interbreed freely at contact zones (reviewed in Utter 2001;Lutz-Carrillo et al 2006;Taylor et al 2007). In fact, interbreeding when no geographic barrier prevails is fundamental to the definition of fish subspecies (Nelson 1999;Haig et al 2006).…”
Section: Ecological Parapatry and Subspecies Differencesmentioning
confidence: 99%
“…For G. d. duebeni, molecular diversity is low with haplotypes shared across broad geographic areas, including the coasts of both N America and Europe. Such a pattern is indicative of taxa experiencing postglacial expansion (Ibrahim et al, 1996;Hewitt, 2000;Fedorov et al, 2003;Lessa et al, 2003). A degree of genetic differentiation does exist among some populations, most noticeably at the species' latitudinal extremes (e.g.…”
Section: Phylogeography Of Gammarus Duebenimentioning
confidence: 99%
“…However, because our data indicates a very recent common ancestor for amphi-Atlantic populations, it seems unlikely that it has in fact persisted in northern areas throughout the Pleistocene. Study of such northern and cold-tolerant taxa is potentially a productive direction for phylogeographic studies aimed at better understanding the response of communities to climate cycles (Fedorov et al, 2003;Hewitt, 2004).…”
Section: Phylogeography Of Gammarus Duebenimentioning
confidence: 99%
“…Considerable geographic structuring of the genetic diversity has been identified in all of them. Distinct phylogeographic structuring has also been observed in many arctic animals, for example, Lemmus spp., Daphnia pulex and Calidris alpina (Weider et al, 1999;Wennerberg, 2001;Federov et al, 2003). However, in some arctic animals, such as the polar fox , the polar bear (Paetkau et al, 1999) and the snowy owl (Marthinsen et al, 2008), there is surprisingly little geographic structuring of the genetic diversity even at the vast circumpolar scale.…”
Section: Introductionmentioning
confidence: 99%